Management of Regional Innovation Development - Demchenko, Sofiia; Barynova, Diana; Zeyu, Liu (Social Economics, 2019)
In modern conditions of dynamically changing environment, questions about new regional ways of innovative development are being updated. Researches confirm that the innovative development of regions is becoming a significant factor in increasing the competitiveness of the region and the formation of high innovative activity. The purpose of the article is to identify the essence of modern approaches to the management of regional innovative development, that are appropriate in the context of transformational changes and to analyze them. To achieve this goal next following tasks have to be done: to study main methods of managing the regional innovative development; to analyze legal and legislative framework; to analyze statistical indicators of innovative development of the region; to identify regions-leaders and regions-outsiders in Ukraine; to study the concept and essence of Smart Specialization Strategies and the entrepreneurial discovery process in the conditions of the Ukrainian regions’ development. The article discusses the competitiveness and efficiency of innovations in a regional context. These are two interrelated economic categories, reflected in their synergistic effect in various areas of the economic and social life of the regions. Their assessment can be carried out at different levels – regional, national and international levels. Regional competitiveness and efficiency of innovation is the result of comprehensive stakeholder actions at these levels. The article also identifies the main obstacles to the management of regional innovation development and analyzes the regulatory and legal framework for the development of innovations at the regional level. The article also carried out a multifactorial comparative analysis based on statistical data of development indicators to assess the development of regions. Regions-leaders and region-outsiders are defined. The article considers the main effective instruments of innovation policy and the most effective ways of its implementation at the regional level. One of the tool is the Smart Specialization Strategy, which aims to grow economically through a strategy based on localization and stakeholder mobilization at the regional level. The paper also studied the entrepreneurial discovery process, that is a «conceptual pillar» of smart specialization.